LEGAL ANALYSIS OF HEALTHY PRODUCT CLAIMS MISLEADING IN THE BAKE N GRIND CASE IN BALI (INTERNATIONAL SEMINAR, 2025)
Misleading health product claims on food labels are a crucial issue in consumer protection in Indonesia. This study analyzes the Bake n Grind case as a concrete example, examining the national legal framework, enforcement effectiveness, and regulatory challenges. Using a juridical-normative approach with a literature review approach, this article examines the implementation of Law Number 8 of 1999 concerning Consumer Protection and Government Regulation Number 69 of 1999 concerning Food Labels and Advertisements, as well as other related regulations. The analysis reveals weak law enforcement, low consumer awareness, and the need for regulatory reform to prevent the practice of misleading claims. Policy recommendations focus on strengthening supervision, consumer education, and harmonizing digital regulations.